The Mechanism of Oral Melatonin Ameliorates Intestinal and Adipose Lipid Dysmetabolism Through Reducing Escherichia Coli-Derived LipopolysaccharideSummary - Bohan Rong (Elsevier, 2021)
Background & Aims: Gut microbiota have been reported to be sensitive to circadian rhythms and host lipometabolism, respectively. Although melatonin-mediated beneficial efforts on many physiological sites have been revealed, the regulatory actions of oral melatonin on the communication between gut microbiota and host are still not clear. Angiopoietin-like 4 (ANGPTL4) has been shown to be strongly responsible for the regulation of systemic lipid metabolism. Herein, we identified that oral melatonin improved lipid dysmetabolism in ileum and epididymal white adipose tissue (eWAT) via gut microbiota and ileac ANGPTL4. Methods: Analyses of jet-lag (JL) mice, JL mice with oral melatonin administration (JL+MT), and the control for mRNA and protein expression regarding lipid uptake and accumulation in ileum and eWAT were made. Gut microbiome sequencing and experimental validation of target strains were included. Functional analysis of key factors/pathways in the various rodent models, including the depletion of gut microbiota, mono-colonization of Escherichia coli, and other genetic intervention was made. Analyses of transcriptional regulation and effects of melatonin on E coli-derived lipopolysaccharide (LPS) in vitro were made. Results: JL mice have a higher level of ileal lipid uptake, fat accumulation in eWAT, and lower level of circulating ANGPTL4 in comparison with the control mice. JL mice also showed a significantly higher abundance of E coli and LPS than the control mice. Conversely, oral melatonin supplementation remarkably reversed these phenotypes. The test of depletion of gut microbiota further demonstrated that oral melatonin-mediated improvements on lipometabolism in JL mice were dependent on the presence of gut microbiota. By mono-colonization of E coli, LPS has been determined to trigger these changes similar to JL. Furthermore, we found that LPS served as a pivotal link that contributed to activating toll-like receptor 4 (TLR4)/signal transducer and activator of transcription 3 (STAT3_/REV-ERBα) signaling to up-regulate nuclear factor interleukin-3-regulated protein (NFIL3) expression, resulting in increased lipid uptake in ileum. In MODE-K cells, the activation of NFIL3 has further been shown to inhibit ANGPTL4 transcription, which is closely associated with lipid uptake and transport in peripheral tissues. Finally, we confirmed that melatonin inhibited LPS via repressing the expression of LpxC in E coli. Conclusions: Overall, oral melatonin decreased the quantity of E coli-generated LPS, which alleviated NFIL3-induced transcriptional inhibition of ANGPTL4 through TLR4/IL-22/STAT3 signaling in ileum, thereby resulting in the amelioration of ileal lipid intake and lower fat accumulation in eWAT. These results address a novel regulation of oral melatonin originating from gut microbiota to host distal tissues, suggesting that microbe-generated metabolites are potential therapies for melatonin-mediated improvement of circadian rhythm disruption and related metabolic syndrome.